Kidney Transplant With Low Levels of DSA or Low Positive B-Flow Crossmatch: An Underappreciated Option for Highly Sensitized Transplant Candidates. Issue 10 (October 2017) - Schinstock, Carrie A.; Gandhi, Manish; Cheungpasitporn, Wisit; Mitema, Donald; Prieto, Mikel; Dean, Patrick; Cornell, Lynn; Cosio, Fernando; Stegall, Mark
Abstract : Background: Avoiding donor-specific antibody (DSA) is difficult for sensitized patients. Improved understanding of the risk of low level DSA is needed. Methods: We retrospectively compared the outcomes of 954 patients transplanted with varied levels of baseline DSA detected by single antigen beads and B flow cytometric crossmatch (XM). Patients were grouped as follows: −DSA/−XM, +DSA/−XM, +DSA/low +XM, +DSA/high +XM, and −DSA/+XM and followed up for a mean of 4.1 ± 1.9 years (similar among groups, P = 0.49). Results: Death-censored allograft survival was similar in all groups except the +DSA/high +XM group, which was lower at 79.1% versus 96.2% in the −DSA/−XM group ( P < 0.01). The incidence of chronic antibody-mediated rejection (CAMR) based on surveillance biopsy was higher with increasing DSA (8.2% −DSA/−XM, 17.0% +DSA/−XM, 30.6% +DSA/low +XM, and 51.2% +DSA/high +XM, P < 0.01), but similar in groups without baseline DSA (8.1% −DSA/−XM vs 15.4% −DSA/+XM, P = 0.19). Having a calculated panel-reactive antibody (cPRA) of 80% or greater was independently associated with CAMR (hazard ratio, 5.2; P = 0.03) even when DSA was undetected at baseline. By 2 years posttransplant, the incidence of CAMR was 19.4% in patients with cPRA of 80% or greater and undetected DSA and negative XM at baseline. Conclusions: Kidney transplantation with low-level DSA with or without a low positive XM is a reasonable option for highly sensitized patients and may be advantageous compared with waiting for a negative XM deceased donor. The risk for CAMR is low in patients with no DSA even if the XM is positive. Patients with cPRA of 80% or greater are at risk for CAMR even if no DSA is detected. Abstract : The authors report results of kidney transplantation in patients with various levels of DSAs detected by single-antigen beads and B flow cytometric crossmatch. Chronic AMR incidence increases with increasing DSA but death-censored allograft survival is similar in all groups but the high DSA level one. Kidney transplantation with low-level DSA is an acceptable option in immunized patients. Supplemental digital content is available in the text.